Problem doboru zmiennych w podejściu modelowym w analizie skupień - Witek, Ewa (Variable Selection for Model-based Clustering, 2009)
We propose a variable selection for model-based clustering using greedy search algorithm. At each stage it searches for the variable to add that most improves the clustering as measured by BIC. As a result the best combination of number of groups and clustering model is chosen (two nested subsets of variables are recast as a model comparison problem). We compare variable selection using greedy search algorithm with a HINoV method of variable selection. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 283-290